Speceis Richness And Diversity Of Amphibians And Reptilians In Pulau Pangkor, Perak, Peninsular Malaysia. - A. Norhayati; R. Nurul Nadiah; M. Nur Izzah Syahirah; J. Nur Johana; B. S. Baizul Hafsyam; Z. Amirah Azizah; A. Amirrudin; Ehwan Ngadi (Forestry Department Peninsular Malaysia, 2024)
Volume :82 No:1